Validation of a scale to assess Facebook dependence - Guedes,Eduardo (2019)
BACKGROUND INFORMATION: Facebook is a social network that has become part of the everyday life of contemporary humanity and is notably the most accessed digital tool, worldwide; through it, one can simultaneously relate to millions of people, as a source of information, communication or entertainment. OBJECTIVE: To produce and validate a scale to evaluate Facebook dependence (FDS). METHOD: Validation was performed in 5 phases: 1- initial scale construction with 20 questions, 2- expert evaluation, 3- application in 200 volunteers, 4- statistical analysis and results, and 5- elaboration of the final 18-question validated version of FDS. RESULTS: We obtained a descriptive statistical analysis, a clear-cut separation of dependents vs. non-dependents and a successful factorial analysis. These results provided a validated version of FDS. CONCLUSIONS: We were able to construct the validated final version of FDS with 18 questions appropriate to the clinical contexts and to be used in conducting research on Facebook dependence. This scale will contribute to future research related to this specific digital dependence, hopefully reducing harmful effects and improving quality of life.